Aortic stenosis and non-cardiac surgery: A systematic review and meta-analysis. (1st August 2017) - Kwok, Chun Shing; Bagur, Rodrigo; Rashid, Muhammad; Lavi, Ronit; Cibelli, Mario; de Belder, Mark A.; Moat, Neil; Hildick-Smith, David; Ludman, Peter; Mamas, Mamas A.
Abstract: Background: Aortic stenosis (AS) poses a perioperative management dilemma to physicians looking after patients who require non-cardiac surgery. The objective of this review is to investigate mortality and adverse cardiovascular events in patients with and without AS who underwent non-cardiac surgery. Methods: We searched MEDLINE and EMBASE for studies that evaluated mortality and adverse cardiovascular events in patients with and without AS who underwent non-cardiac surgery. Pooled risk ratios for mortality and adverse outcomes (myocardial infarction, stroke, heart failure, death) were calculated using the dichotomous analysis method and subgroup analysis was performed considering the effect of severity of AS and symptoms. Results: We identified 9 relevant studies with 29, 327 participants. Among studies of severe AS, there was no significant difference in mortality (RR: 1.49, 95%CI:0.85–2.61; P = 0.16) associated with non-cardiac surgery, but there was a significant increase in the composite adverse outcome (RR: 2.30, 95%CI:1.33–3.97; P = 0.003). When the analysis involved any other degree of AS, eight studies were included and the pooled results showed a significant increase in composite adverse outcome (RR: 1.64, 95%CI:1.23–2.19; P < 0.001) and myocardial infarction (RR: 1.90, 95%CI:1.54–2.34; P < 0.001). When patients with asymptomatic AS were considered, the pooled results of four studies suggested an increased risk of composite adverse outcomes (RR: 1.59, 95%CI:1.19–2.12; P = 0.002) but not mortality, myocardial infarction, heart failure or stroke. Conclusions: Patients with AS undergoing non-cardiac surgery have not been shown to be at increased risk of mortality, but have significantly higher rates of adverse cardiovascular events compared to patients without AS. Highlights: It is unclear if patients with aortic stenosis (AS) can safely undergo non-cardiac surgery. Our results seem to show that non-cardiac surgery is not associated with mortality in patients with severe AS. However, there are more adverse cardiovascular events with non-cardiac surgery. An individualized, patient-centred approach is of paramount importance in identifying patients at higher risk.